PENGARUH LINGKUNGAN KERJA, STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI LPD DESA ADAT TEMBAWU - I Made Adhika; Ni Made Dwi Puspitawati; Putu Agus Eka Rismawan (VALUES, 2023)
The existence of LPD, especially in Tembawu Traditional Village, is a village-owned business agency which is a financial institution that assists the indigenous village communities both in the present and in the future. Thus, at first glance, this work is more centered on service. This study was intended to determine and analyze the effect of the work environment, work stress, and workload on the performance of employees in the Tembawu Traditional Village LPD. The population in this study were the whole employees of the Tembawu Traditional Village LPD. In collecting the sample in this study, it used the census sampling method that obtained 38 respondents. The analytical method used in this study was multiple linear regression analysis. The results of this research demonstrated that the work environment, work stress, and workload had a partial effect on the performance of employees in the LPD of the Traditional Village of Tembawu. It could be acknowledged that the work stress variable had a negative effect on employee performance, as well as the work environment, and workload variables had a positive influence on the performance of employees in the Tembawu Traditional Village LPD. Therefore, it was necessary to improve communication between employees so as not to cause quarrels, and cooperation between employees was needed in order to achieve work targets in the Tembawu Traditional Village LPD.